Terpenoids From Cannabis Do Not Mediate an Entourage Effect by Acting at Cannabinoid Receptors - Finlay, David B.; Sircombe, Kathleen J.; Nimick, Mhairi; Jones, Callum; Glass, Michelle (Frontiers in Pharmacology, 2020)
The Entourage Effect is a proposed explanation for biological observations (both in vitro and in vivo) that some cannabinoid ligands' activities can be modified by compounds with which they are expressed natively. While more supporting data for this phenomenon is available for endocannabinoids than phytocannabinoids derived from the cannabis plant, an increasing volume of anecdotal reports and interest in the plant have provoked research into the activity of minor chemical constituents of the plant -including volatile terpenoids such as myrcene, α-and β-pinene, β-caryophyllene, and limonene. A source of difficulty in developing the Entourage Effect hypothesis is the lack of a proposed mechanism; studies conflict as to whether the effect is directly receptor-mediated or can be explained by different types of functional interaction in vitro or in vivo. The current study was designed to help determine whether terpenes in the cannabis plant have detectable receptor-mediated effects -both at the level of receptor interaction (using a standard radioligand binding paradigm with ability to detect both orthosteric and allosteric interactions of test compounds) and receptor function in transfected HEK cells (using a BRET assay, CAMYEL, for cyclic AMP signalling; a canonical CB1 and CB2 signalling pathway highly sensitive to functional modulation). With the possible exception of a weak interaction of β-caryophyllene with CB2, no data were produced to support the hypothesis that any of the five terpenes tested (either alone or in mixtures) have direct interactions with CB1 or CB2, as the binding of none of radioligand ([ 3 H]-CP55,940), Δ 9 -tetrahydrocannabinol, or cannabidiol were altered by the presence of terpenes. Similarly, terpene functional effects were also not detected, either alone or in combination with Δ 9 -tetrahydrocannabinol, 2-arachidonoyl glycerol, or cannabidiol. As evidence is building that the putative Entourage Effect cannot be explained by direct effects at CB1 or CB2, is it clear that other explanations for these observations must be explored.